Ferroptosis and musculoskeletal diseases: “Iron Maiden” cell death may be a promising therapeutic target - Zhang, Yili; Huang, Xinyi; Qi, Baoyu; Sun, Chuanrui; Sun, Kai; Liu, Ning; Zhu, Liguo; Wei, Xu (Frontiers in Immunology, 2022)
Ferroptosis is a novel form of cell death precisely regulated by iron metabolism, antioxidant processes and lipid metabolism that plays an irreplaceable role in the development of many diseases. Musculoskeletal disorders (MSKs), including osteoporosis, osteoarthritis, rheumatoid arthritis, intervertebral disc degeneration, sarcopenia, and rhabdomyolysis, have become one of the most common causes of disability and a major burden on public health and social care systems. The mechanism of ferroptosis in MSKs has recently been elucidated. In this review, we briefly introduce the ferroptosis mechanism and illustrate the pathological roles of ferroptosis in MSKs with a focus on how ferroptosis can be exploited as a promising treatment strategy. Notably, because the toxicity of compounds that inhibit or induce ferroptosis in other organs is largely unknown, ferroptosis appears to be a double-edged sword. We believe that more research is needed in the future to verify the therapeutic effects based on ferroptosis in MSKs.